Metal-Free Synthesis of C-3-Alkoxycarbonylated 2H-Indazoles Using Alkyl Carbazates - Lai, Dipti; Bhattacharjee, Suvam; Ghosh, Sumit; Sinha, Subrata; Hajra, Alakananda (Synlett, 2024)
A simple, efficient, and environmentally benign method for the direct C-3-alkoxycarbonylation of 2H-indazoles using alkyl carbazates has been developed under metal-free conditions at room temperature. This current protocol represents a facile access to C-3-carboxylic ester derived 2H-indazoles with wide functional group tolerance in good to excellent yields. The mechanistic studies suggest that the reaction proceeds through a radical pathway.
Keywords: metal-free; C-3-alkoxycarbonylation; 2H-indazole; synthetic transformations; alkyl carbazate